Coronary Artery Calcification on Thoracic Computed Tomography Is an Independent Predictor of Mortality in Patients With Bronchiectasis. Issue 3 (May 2021) - Williams, Michelle C.; van Beek, Edwin J.R.; Hill, Adam T.; Murchison, John T.
Abstract : Purpose: Coronary artery calcification (CAC) on thoracic computed tomography (CT) can identify patients at risk of coronary artery disease (CAD) mortality. However, the overlap between bronchiectasis and CAC severity for predicting subsequent outcomes is unknown. Materials and Methods: CT images from 362 patients (mean age 66±14 y, 38% male) with known bronchiectasis were assessed. Bronchiectasis severity was assessed using the Bronchiectasis Severity Index (0 to 4, mild; 5 to 8, moderate; and ≥9, severe). CAC was assessed with a visual ordinal score (0, none; 1, mild; 2, moderate; 3, severe) in each of the left main stem, left anterior descending, left circumflex, and right coronary arteries. Vessel CAC scores were summed and categorized as none (0), mild (1 to 3), moderate (4 to 8), and severe (9 to 12). Results: Patients with severe bronchiectasis were older ( P <0.001), but were not more likely to have a history of CAD, hypertension, or smoking. CAC was present in 196 (54%). Over a mean of 6±2 years, 59 (16%) patients died. Patients with moderate or severe CAC were 5 times more likely to die than patients without CAC (hazard ratio: 5.49, 95% confidence interval: 2.82-10.70, P <0.001). Patients with severe bronchiectasis were 10 times more likely to die than patients with mild bronchiectasis (hazard ratio: 10.11, 95% confidence interval: 4.22-24.27, P <0.001). CAC and bronchiectasis severity were independent predictors of mortality, but age, sex, smoking, and history of CAD or cerebrovascular disease were not. Conclusions: CAC is common in patients with bronchiectasis, and both CAC and bronchiectasis severity are independent predictors of mortality.